Development and experimental study of a supercritical CO2 axial turbine applied for engine waste heat recovery. (1st January 2020) - Huang, Guangdai; Shu, Gequn; Tian, Hua; Shi, Lingfeng; Zhuge, Weilin; Zhang, Jing; Atik, Mohammad Atikur Rahman
Graphical abstract: Highlights: A 4.5 kW supercritical CO2 axial turbine expander is proposed. A maximum power generation 2.27 kW is obtained. A maximum rotational speed 41584 rpm is obtained. Influence factors on the performance of turbine expander are investigated. Abstract: CO2 -based transcritical power cycle (CTPC) has been proposed as a suitable engine waste heat recovery (E-WHR) technology with the advantage of miniaturization and good recovery capacity. Expander, as the core power conversion device, is of great importance to the overall cycle performances. The main purpose of this paper is to conduct dynamic tests of the proposed turbine expander, with focus on the turbine operational characteristics and performance. In this study, a partial admission axial turbine expander coaxial with a high-speed synchronous generator is designed and manufactured considering the thermodynamic properties of supercritical CO2 . The geometry of the turbine is 56 mm rotor diameter, 4 mm blade height, and 39000 rpm of operating speed at the inlet design condition of 10 MPa and 230 °C, outlet condition of 6 MPa and mass flow rate of 0.18 kg/s. The performance of the developed turbine expander and CTPC system with respect to the rotational speed and mass flow rate are investigated experimentally. Based on the experimental data, the maximum rotational speed of the the turbine reaches 41584 rpm and the turbine expander generated maximum power 2.27 kW at 20878 rpm. The power capacity of the turbine increases to the maximum value first and then decreases with the increase of rotational speed as well as the isentropic efficiency. The power generation of the turbine expander is proportional to pressure ratio as well as mass flow rate.